An analysis of meteorological parameters influencing solar drying systems in Algeria using the isopleth chart technique. (July 2018) - Benseddik, A.; Azzi, A.; Chellali, F.; Khanniche, R.; Allaf, k.
Abstract: In the current contribution identifications of different climate areas existing in Algeria, as categorized by Borel [1], are made. Meteorological parameters that have direct impact on solar dryer design were modelled and performances were explored and extracted from a database established by a software package named Meteonorm ® . More particularly, interest was made on parameters of utmost importance namely, solar irradiation intensity, ambient temperature and air relative humidity. A so called isopleth charts showing clearly contrasts existing between different studied sites were plotted. They also provided solid bases to solar drier designer in Algeria. Also the concept of PDF (Probability Density Function) was introduced to estimate the distribution of different variables. Highlights: Elaborated isopleth improved parameters description directly influencing solar dryer. Analysis using solar resources to outline climate contrast between studied cities. Studied cities favor use of solar energy reducing cost and need of electrical network. Probability Density Function is introduced to estimate distribution of variables. The isopleth charts form bases for renewable energy system designer.